Quantification of CDR1 Gene Expression in Fluconazole Resistant Candida Glabrata Strains Using Real-time PCR - Shadi SHAHROKHI; Fatemeh NOORBAKHSH; Sassan REZAIE (Tehran University of Medical Sciences, 2017)
Background: The opportunistic fungi, particularly Candida glabrata has been known as main etiologic agents of life-threating infections in some patients. Although fluconazole is the most effective antifungal agent against candidiasis, C. glabrata, fluconazole-resistant strains have been increased recently overexpression or mutations of ATP-binding cassette (ABC) transporter family membrane proteins such as; Cg CDR1, Cg CDR2 are responsible for fluconazole resistance in a large proportion of candidiasis cases. The aim of this study was to evaluate CDR1 gene expression level as one of main mechanism involved in this resistance using. Methods: Candida glabrata strains were collected from various clinical samples in hospitals of Tehran in 2015 . After validation of all isolates by conventional and molecular methods, the susceptibility analysis to fluconazole of all isolates was performed using CLSI broth microdilution M27-A3 and M27-S4 protocols. Two isolates have been selected based on difference in susceptibility and CDR1-mRNA expression level of isolates was measured by Real-time PCR method. Results: Susceptibility results revealed that 32%, 64% and 4% of strains were susceptible, dose-dependent (DD) and resistant to fluconazole respectively. Furthermore, resistance strain of C. glabrata (MIC≥64 µg/ml) showed overexpression of CDR1 compared with sensitive strain in Real-time PCR analysis. Conclusion: Thus, it is necessary to investigate the functions of CgCDR1 genes as a transporter-related gene.